تأثير معوِّقات استخدام نظم المعلومات التسويقيَّة على جودة القرارات التسويقيَّة "دراسة ميدانيَّة على فروع شركة (Syriatel) العاملة في السَّاحل السُّوري" - نصّور ريزان; إسبر سعيد; أحمد ديالا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف هذا البحث إلى تحديد مدى تأثير معوِّقات استخدام نظم المعلومات التسويقيَّة (المعوِّقات المتعلِّقة بمتَّخذ القرار، المعوِّقات المتعلِّقة بنظم المعلومات التسويقيَّة ذاتها، المعوِّقات المتعلِّقة بالمؤسَّسة المدروسة، والمعوِّقات المتعلِّقة بالبيئة الخارجيَّة) على جودة القرارات التسويقيَّة، وذلك في عيِّنة من فروع شركة (Syriatel) العاملة في السَّاحل السُّوري. قامت الباحثة بتوزيع (108) استبياناً على المديرين ورؤساء الأقسام والمراقبين وأفراد الكوادر الإداريَّة المسؤولة عن اتِّخاذ أشكال وأنواع مختلفة من القرارات التسويقيَّة في الفروع محل الدراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (88) استبانة. قامت الباحثة بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّلت الباحثة إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لجميع معوِّقات استخدام نظم المعلومات التسويقيَّة المدروسة (المعوِّقات المتعلِّقة بمتَّخذ القرار، المعوِّقات المتعلِّقة بنظم المعلومات التسويقيَّة ذاتها، المعوِّقات المتعلِّقة بالمؤسَّسة المدروسة، والمعوِّقات المتعلِّقة بالبيئة الخارجيَّة) على جودة القرارات التسويقيَّة في الفروع محل الدراسة. كما تقدَّمت الباحثة في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: حث المديرين ومتَّخذي القرارات في الفروع محل الدراسة على استخدام نظم المعلومات التسويقيَّة كأساس في عملية اتخاذ القرارات التسويقيَّة، والاهتمام بتدريب المدراء ومتَّخذي القرارات والعاملين في تلك الفروع على استخدام هذه النظم، فضلاً عن ضرورة تطوير الأساليب الإداريَّة في الفروع محل الدراسة والمتعلِّقة بتخفيض درجة مركزية وروتينية القرارات وتنظيم قنوات الاتصال من أجل توفير نظام متكامل للمعلومات يكون قادراً على تزويد متخذي القرارات التسويقيَّة بالمعلومات والبيانات الدقيقة والَّلازمة لاتِّخاذ القرارات التسويقيَّة في الوقت المناسب. This research was conducted to determine the effect of constraints on the use of marketing information systems (constraints related to decision makers, constraints related to marketing information systems itself, constraints related to the studied company, and constraints related to external environment) on the quality of marketing decisions in a sample of (Syriatel) branches operating in the syrian coast. The researcher distributed (108) questionnaires to managers, heads of departments, supervisors and administrative personnel responsible for taking various forms and types of marketing decisions. The number of valid questionnaires that were discharged was (88). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which are: There is a significant effect on all the constraints of using the marketing information systems (constraints related to decision makers, constraints related to marketing information systems itself, constraints related to the studied company and external environment constraints) on the quality of marketing decisions in the studied branches. The researcher also made a number of recommendations, including: To encourage managers and decision makers in the branches under study to use marketing information systems as a basis in the decision making process, and to take care of the training of managers, decision makers and employees in these branches to use these systems, as well as the need to develop the administrative methods in the branches under study, And the organization of channels of communication in order to provide an integrated information system capable of providing decision makers with accurate information and data necessary to make marketing decisions in a timely manner.